The spatiotemporal patterns and network characteristics of emissions embodied in the international trade of livestock products. (15th November 2022) - Wang, Xiang; Qiang, Wenli; Liu, Xiaojie; Yan, Simin; Qi, Yumei; Jia, Zhuo; Liu, Gang
Abstract: Livestock production is greenhouse gas (GHG) emission intensive, and thus the increasing international trade of livestock products in recent decades has resulted in increased embodied emissions. Considering the varying emission intensity in production in different countries and the expected further increase in livestock product trade in the future, it becomes crucial to understand the spatial and temporal dynamics of such embodied GHG emissions for climate change mitigation in the livestock sector. In this study, we aimed to address such gaps and analyzed the spatiotemporal patterns and network characteristics of GHG emissions embodied in the international trade of seven major categories of livestock products among 228 world economies during 1986–2017. The results showed that the total volume of GHG emissions embodied in livestock product trade reached 92.0 MT in 2017, accounting for 2.6% of the total emissions from livestock production. Sheep meat has replaced cattle meat as the major contributor to embodied emissions. In 2017, the largest flows of embodied emissions were within Europe, followed by the flows from Oceania to Asia. The fluxes in intra-upper middle and intra-high-income economies accounted for most of the total embodied emissions. Although the global average emission intensity of livestock production declined in these four decades, the trade flows from high to low emission intensity economies increased, especially for cattle and sheep meat. This resulted in an overall increase of contribution from the global livestock trade in GHG emissions from the global livestock sector. Therefore, effective measures and policies must be designed from both consumption and production perspectives to ensure proper accounting of these embodied emissions and maximize the reduction potential for a sustainable food system transition. Highlights: Increasing trade of livestock products resulted in increasing embodied emissions. The network characteristics of such embodied emission flows have been revealed. The largest embodied emission flows are within Europe and from Oceania to Asia. Trade flows from high to low emission intensity economies have increased. The embodied emissions deserve more policy attention towards sustainable food systems.